Op amp applications handbook. - Jung, Walt, ....- (Amsterdam : Elsevier, 2006)
Table of Contents Op amp history highlights Ch. 1 Op amp basics Ch. 2 Specialty amplifiers1 Ch. 3 Using op amps with data converters Ch. 4 Sensor signal conditioning Ch. 5 Analog filters Ch. 6 Signal amplifiers Ch. 7 Hardware and housekeeping techniques Ch. 8 Op amp history